Comparison of Phytochemical Profile and In Vitro Bioactivity of Beverages Based on the Unprocessed and Extruded Sesame (Sesamum indicum L.) Seed Byproduct - María Fernanda Quintero-Soto; Ramona Julieta Espinoza-Moreno; Jennifer Vianey Félix-Medina; Fernando Salas-López; Cruz Fernando López-Carrera; Oscar Daniel Argüelles-López; Martha Elena Vazquez-Ontiveros; Mario Armando Gómez-Favela (Foods, 2022)
In this research functional beverages based on the unprocessed and extruded sesame seeds byproduct were fabricated; phytochemical profile, antioxidant, antidiabetic, and hypoglycemic potential were evaluated. Twenty-four phytochemical compounds were identified in total in both beverages; fourteen of the phytochemical compounds were not modified by the extrusion process. Seventeen of the 24 compounds were identified in the unprocessed sesame seeds byproduct flour beverage−10% (UB10) and 21 in the extruded sesame seeds byproduct flour beverage−10% (EB10). The compounds only identified in UB10 are caffeic acid, luteolin-7-O-glucoside, and isorhamnetin; and in EB10 those compounds were vanillic acid, acteoside, luteolin, quercetin, and melanoidins. No significant difference was observed in the content of total phenolic compounds (TPC) (14.90 and 15.97 mg GAE/100 mL) and total flavonoids (TF) (5.37 and 5.85 mg QE/100 mL). An increase in the biological activity of ESFB10 (IC50: ABTS = 0.19, DPPH = 0.21, α-amylase = 1.01, α-glucosidase = 0.17, DPP4 = 0.11 mg/mL) was observed, compared to UB10 (IC50: ABTS = 0.24, DPPH = 0.31, α-amylase = 2.29, α-glucosidase = 0.47, DPP4 = 0.30 mg/mL). Therefore, the extrusion process had a positive effect, which displayed the highest efficiency inhibiting the free radicals and enzymes related to carbohydrate metabolism.